World Economic Outlook, May 1994. (World Economic Outlook; World Economic Outlook ;, 1995)
The World Economic Outlook presents the IMF staff's analysis and projections of economic developments at the global level, in major country groups (classified by region, stage of development, et cetera), and in many individual countries. It focuses on major economic policy issues as well as on the analysis of economic developments and prospects. It is usually prepared twice a year, as documentation for meetings of the International Monetary and Financial Committee, and forms the main instrument of the IMF's global surveillance activities.